алгебра 7 класс

Номер 103

 

Условие:

Упростите выражение:
а) (х - 1) + (12 - 7,5x);
б) (2р + 1,9) - (7 - р);
в) (3 - 0,4а) - (10 - 0,8а);
г) b - (4 - 2b) + (Зb - 1);
Д) У - (У + 4) + (у - 4);
е) 4x - (1 - 2x) + (2x - 7).

 

Ответ:

a) (x - 1) + (12 - 7,5x) = x - 1 + 12 - 7,5x = (x - 7,5x) + (12 - 1) = -6,5x + 11;
б) (2p + 1,9) - (7 - p) = 2p + 1,9 - 7 + p = (2p + p) + (1,9 - 7) = 3p - 5,1;
в) (3 - 0,4a) - (10 - 0,8a) = 3 - 0,4a - 10 + 0,8a = (-0,4a + 0,8a) + (3 - 10) = 0,4a - 7;
г) b - (4 - 2b) + (3b - 1) = b - 4 + 2b + 3b - 1 = (b + 2b + 3b) - (4 + 1) = 6b - 5; .
д) У - (У + 4) + (y - 4) = y - y - 4 + y - 4 = (y - y + y) - (4 + 4) = y - 8;
e) 4x - (1 - 2x) + (2x - 7) = 4x - 1 + 2x + 2x - 7 = (4x + 2x + 2x) - (1 + 7) = 8x - 8.